TINJAUAN YURIDIS TERHADAP PENYALAHGUNAAN LEM FOX OLEH ANAK JALANAN DAN REMAJA SEKOLAH (STUDI KASUS DI KOTA SAMARINDA) - Muhammad Iqbal (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT This study aims to determine the factors that led to that street children and adolescents abusing school glue fox and to determine measures to be taken to prevent its misuse.This research was conducted in the city of Samarinda precisely in Samarinda Police Office as well as on various roads or gathering place for street children and adolescents of school.The method used is qualitative case study approach with interview techniques.Results of the study authors, there are factors that encourage street children and adolescents abusing school glue fox in the city of Samarinda namely that the dominant factor is the influence of the environment both in neighborhoods and schools, and also due to the inability to buy drugs are relatively expensive and not according to ability economy of street children and adolescents of school as a user, so as an alternative to using addictive substances were relatively easy to obtain dangerous to inhale glue the fox, but it is also due to the curiosity of the fox glue itself  so began to try and finally addiction, as well as other reasons due less harmonious family relationships, so that led to the abuse of glue fox as a fugitive on the issue.In getting solution the abuse of fox glue, Pre-emptive efforts had only limited to providing education or enlightenment about the dangers of narcotics and other addictive substances to parents and pupils in various schools in the city of Samarinda, Preventive efforts also in the form of a routine patrol and surveillance accompanied by police raids assisted Satpol PP around the streets of the city of Samarinda, and last Repressive efforts to curb, the return of children to parents along with a warning as well as the construction of a rehabilitation center for drug users and other addictive substances including for abusers glue fox, so that the effort required of all three increased functionality and support as well as community participation. Keywords:  fox glue, addictive